Spolne zlorabe - Šraj, Tanja (Psihološka obzorja (Ljubljana), 2010)
Professionals have shown extreme interest in psychological consequences of sexual abuse for more than 20 years. Besides researching consequnces of an abuse, thier interest has also been focused on relations to other characteristics of sexual abuse. We examined correlations of short-term and long-term consequences of sexual abuse with time variables (age of the victim at the beginning, ending and disclosure of sexual abuse, duration of sexual abuse) and support of the victim after disclousure in the sample of 78 victims of sexual abuse.Results suggest the correlation between age of the victim with some of the long-term consequences. There is tendency toward positive correlation between duaration of sexual abuse and long-term consequences. The support of the victim negativly correlated with long-term consequences. We suggest further research on the consequences and other characteristic of sexual abuse on a larger sample.
Keywords: spolne zlorabe; child; otroci; psihične posledice